Psychological perspectives on crowding: A materialist critique - Eichhorn, Henk (PINS-Psychology in Society, 2025)
Social and environmental psychologists engaged in crowding research have traditionally employed idealist rather than materialist perspectives. This paper argues that idealist perspectives have a number of fundamental shortcomings which inhibit their ability to come to grips with their subject matter.